Implementation of the Internet of Things using Blynk platform for smart home - Qolbina Burhan, Akram; Islami, Syaiful (Department of Electrical Engineering Universitas Negeri Padang, 2024)
This research develops an Internet of Things (IoT)-based Smart Home system using the Blynk platform and the ESP32 microcontroller. The system is designed to facilitate remote control of household electronic devices through a smartphone application, thereby optimizing energy use and enhancing efficiency. In its implementation, the ESP32 serves as the main connector of electronic devices to the internet, while relays are used to control the power of devices like lights. This system not only increases user convenience but also reduces the risk of household accidents caused by devices left on unintentionally. The research results show that users can monitor and control device status in real time, potentially lowering monthly electricity costs. This system is considered suitable for application in smart homes, providing easy, efficient, and safe remote control